(3CSGSjGJ GdJLGQI GdOhdjI GdeYGUQI (B:s (3ef GdejRI GdeWdbI Gdi GdYhdeI hGdMQjI hGdQaGgjI GdGbJUGOjI (B/s - (3GdUQf, QYO MSfs ((3OeTb(B: s (3OGQ GdQVG ddfTQ(B, s, 2000)
(3ebOeI aj GdJLGQI GdOhdjI,bVGjG heSGFd gGeI aj GdJLGQI GdOhdjI,GdYhdeI hBKGQgG Ydi GdJLGQI GdOhdjI,GdfXQjGJ GdJbdjOjI aj GdJLGQI GdOhdjI,GdfXQjGJ GdMOjKI ddJLGQI GdOhdjI,eYOd GdJHGOd hGdecGSH ef GdJLGQI GdOhdjI,SjGSGJ GdJLGQI GdOhdjI,ejRGf GdeOahYGJ,GdYdGbGJ GdfbOjI GdOhdjIs
(3agQS GdeUWdMGJ(B:(3U(B.397-401(3; HHdjhZQGajG(B:(3U(B.403-410 (3agQS GdLOGhd(B:(3U(B.411(3; agQS GdCTcGd(B:(3U(B.413s
Keywords: (3GdJLGQI GdNGQLjIs; (3GdYhdeIs